Stimulus-Organism-Response Framework in Action: Exploring the Impact of Shopee's AR Features on Prosumer Behaviour in Beauty Products - Kholifah, Kholifah (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyse the influence of Augmented Reality (AR) technology in the Shopee e-commerce platform, specifically the BeautyCam feature, on consumer behaviour in the beauty product sector. Using the Stimulus-Organism-Response (SOR) model, this study examines how AR technology as an external stimulus affects consumer perceptions and emotions, which in turn impact purchasing decisions and prosumer engagement. The main focus is on the consumer experience in selecting products such as lipstick, foundation, and skincare without physically trying them, as well as the role of AR in enhancing trust and personalisation in shopping. Respondents consist of active Shopee users who have used the AR feature and contributed to reviews or content related to beauty products. The research was conducted through an online questionnaire combining qualitative and quantitative data. The expected results include identifying the positive influence of AR on self-confidence, consumer satisfaction, prosumer engagement, and consumer loyalty. These findings are expected to provide strategic recommendations for Shopee and other e-commerce platforms in optimising the use of AR technology to enhance shopping experiences and the effectiveness of beauty product marketing.Top of Form